Lifestyle and Genetics in Obesity and type 2 Diabetes - Temelkova-Kurktschiev, T.; Stefanov, T. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Obesity and type 2 diabetes mellitus are multifactorial health threats caused by a complex interplay between genetic predisposition and the environment with dramatically increasing worldwide prevalence. The role of heritability in their etiology is well recognized, however, the numerous attempts made in order certain genetic variants determining individual susceptibility to be identified have had limited success, until recently. At present the advancements in human genetics and the utilization of the genome-wide association approach have led to the identification of over 20 genetic loci associated with, respectively obesity and type 2 diabetes. Most of the genes identified to date, however, have modest effect on disease risk suggesting that both diseases are unlikely to develop without the individual being exposed to obesity- and/or type 2 diabetes-promoting environment. Indeed, unhealthy lifestyle, characterized by physical inactivity and food overconsumption is an unequivocally established risk factor for obesity and type 2 diabetes. Numerous epidemiological studies and randomized controlled trials, on the other hand, have demonstrated that lifestyle modification is effective in obesity and type 2 diabetes prevention. Furthermore, gene-lifestyle interaction studies suggest that genetic susceptibility to obesity and type 2 diabetes may be partially or totally kept under control by healthy lifestyle or lifestyle modification and that lifestyle determines whether an individual is likely to develop the disease. Inherited factors, however, seem to influence individual response to a lifestyle intervention program and even the motivation for lifestyle change. Personalized interventions according to genotype may be, therefore, considered in the future. By then lifestyle modification targeting dietary change and increased physical activity may be recommended for successful obesity and type 2 diabetes prevention irrespectively of genetic susceptibility.
Keywords: genetics; lifestyle; obesity; type 2 diabetes